Optimizing alkaline sizing in sugar cane bagasse paper recycling - Molina Tirado, Liliana Beatriz (2009)
The objective of this work was the variation of additives dosage in the sizing treatment of sugar cane bagasse paper for liners and flutings, on taking into account the cycles of use, for reaching the same sizing degree in each cycle. The degradation of the physical properties under different conditions of relative humidity and temperature for each stage of the papermaking cycle was also studied. The sizing agent utilized was the alkyl ketene dimer (AKD). Cationic starch and a retention agent (a modified high molecular weight polyethylenimine) were also added. The experimental design applied was a Central Composite Design (CCD). Once the optimum dosage of additives found, the sheets were submitted to different conditions of humidity and temperature, and their physical properties were tested. Three papermaking cycles were carried out: a papermaking cycle, followed by two recycles. It was observed that a lower amount of AKD was required to reach the water absorption objective (measured by the Cobb120 test), as it progresses during the papermaking cycles, and also that good properties in liner and fluting paper could be attained in spite of the recycles, although, at 75% relative humidity (RH), the liner and fluting properties drastically decreased